Institutional Environment of Small Private Enterprises in Vetnam - Cao Thuy Xiem; Truong Doan The (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
The paper examines institutional environment in which small private enterprises operate in Vietnam. The quantitative research was conducted to identify advantageous and disadvantageous factors of the institutional environment. Generally speaking, at the institutional level the environment has been improved, however differences between de jure and de facto improvements still there. While at the organizational level the least improved environmental factor was limited management’s competence. The research proposed the further reform of institutional environment should emphasize enforcement characteristics and the support by government to upgrade management’s competence should be in right time and right place.